Substituição parcial de farelo de soja por grãos de destilaria de alta proteína com levedura para vacas em lactação - Dias, Julia Diane Lima (2021)
This experiment evaluated the partial replacement of soybean meal (SBM) with distillers dried grains with yeast (DDGY) at the same diet crude protein (CP) content for dairy cows. Compared to SBM (49.2% CP), the DDGY (50.2% CP) had higher in situ rumen undegradable CP (RUP) and lower in vitro RUP intestinal digestibility. Thirty-two Holstein cows were individually fed a standard diet for 2 weeks and treatments control (CTL) or DDGY for 8 weeks. Diets had 16.7% CP and the inclusion of SBM was 17.8% in CTL and 11.6% in DDGY. In the DDGY diet, the inclusion of DDGY was 6.3%, representing 3.3% of diet CP. Data were analyzed with a repeated measures approach. Significance was declared at P ≤ 0.05 and trends at 0.05 < P ≤ 0.10. There was no significant interaction between treatment and time for any variable measured over time. The DDGY increased milk yield (32.2 vs 31.3 kg/d) at similar dry matter intake (DMI; 22.3 kg/d), increasing the milk to intake ratio (1.48 vs 1.42). The positive effect of DDGY on milk yield was fast acting and consistent throughout the experiment. The DDGY tended to increase the yields of milk casein and protein. The concentrations in milk and the daily yields of fat and lactose did not differ. The DDGY reduced urea-N in milk (14.1 vs 17.1 mg/dL) and plasma (16.5 vs 19.1 mg/dL, average of 0, 2, 4, 8, 12, 16, and 20 hours post-feeding). The total tract apparent digestibility of dry matter, organic matter, starch, and neutral detergent fiber, rumen microbial yield, and plasma glucose concentration did not differ. The DDGY tended to reduce eating time (272 vs 299 min/d) and had no effect on rumination time (460 min/d). The DDGY increased the proportion of daily intake in the afternoon (44.0 vs 37.6%). In the morning (0700-1300 h), DDGY increased the refusal for feed particles > 19 mm (69.3 vs 93.7% of predicted intake) and the selection in favor of particles < 8 mm (120 vs 101% of predicted intake). The frequency, duration, and size of meals did not differ. The partial replacement of SBM with DDGY had no effect on diet digestibility, intake, and rumen microbial yield, affected eating behavior, improved milk yield and feed efficiency, and reduced plasma and milk urea-N, supporting the in situ estimation of higher RUP supply in DDGY than in SBM.